Gender-specific application behavior, matching, and the residual gender earnings gap - Benjamin Lochner; Christian Merkl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2022)
This paper opens up the black box of gender-specific application and hiring behavior and its implications for the residual gender earnings gap. To understand the underlying mechanisms, we propose a two-stage matching model with testable implications. Using the German IAB Job Vacancy Survey, we show that the patterns in the data are in line with linear and nonlinear production functions at different jobs. Women's application probability at high-wage firms is much lower than at low-wage firms. By contrast, women have the same probability of being hired as men when they apply at high-wage firms. These patterns are not in line with taste-based discrimination, but they can be rationalized by high-wage firms that ask for more employer-sided flexibility. We show that the share of male applicants increases in various dimensions of employer-sided flexibility requirements. Adding the share of male applicants as a proxy for flexibility requirements to Mincer wage regressions reduces the residual earnings gap by around 50 to 60 percent. Women who match at jobs with a high share of male applicants earn substantially more than women at comparable jobs with only females in the application pool (due to compensating differentials). By contrast, when women with children match at these jobs, they face large earnings discounts relative to men.
Keywords: E24; J16; J31; 330; Job Search; Application Behavior; Gender Earnings Gap